The therapeutic usage of botulinum toxin (Botox) in non-cosmetic head and neck conditions - An evidence based review - Kamran Habib Awan (Elsevier, 2017)
Botulinum toxin (Botox) is an exotoxin produced from Clostridium botulinum. It blocks the release of acetylcholine from the cholinergic nerve end plates resulting in inactivity of the muscles or glands innervated. The efficacy of Botox in facial aesthetics is well established; however, recent literature has highlighted its utilization in multiple non-cosmetic medical and surgical conditions. The present article reviews the current evidence pertaining to Botox use in the non-cosmetic head and neck conditions. A literature search was conducted using MEDLINE, EMBASE, ISI Web of Science and the Cochrane databases limited to English Language articles published from January 1980 to December 2014. The findings showed that there is level 1 evidence supporting the efficacy of Botox in the treatment of laryngeal dystonia, headache, cervical dystonia, masticatory myalgia, sialorrhoea, temporomandibular joint disorders, bruxism, blepharospasm, hemifacial spasm and rhinitis. For chronic neck pain there is level 1 evidence to show that Botox is ineffective. Level 2 evidence exists for vocal tics and trigeminal. For stuttering, facial nerve paresis, Frey's syndrome and oromandibular dystonia the evidence is level 4. Thus, there is compelling evidence in the published literature to demonstrate the beneficial role of Botox in a wide range of non-cosmetic conditions pertaining to the head and neck (mainly level 1 evidence). With more and more research, the range of clinical applications and number of individuals getting Botox will doubtlessly increase. Botox appears to justify its title as 'the poison that heals'.